Quantification of docetaxel and its metabolites in human plasma by liquid chromatography/tandem mass spectrometry. (19th July 2013) - Hendrikx, J. J. M. A.; Dubbelman, A. C.; Rosing, H.; Schinkel, A. H.; Schellens, J. H. M.; Beijnen, J. H.
Abstract : RATIONALE: During drug development accurate quantification of metabolites in biological samples using mass spectrometry is often hampered by the lack of metabolites of chemically pure quality. However, quantification of metabolites can be useful for assessment and interpretation of (pre)clinical data. We now describe an approach to quantify docetaxel metabolites in human plasma by liquid chromatography/tandem mass spectrometry (LC/MS/MS) using docetaxel calibration standards. METHODS: Metabolites (M1/M3, M2 and M4) were generated using microsomal incubations. Retention times of docetaxel and its metabolites were assessed using an LC/UV assay and peak identification was performed by LC/MS n . Samples containing isolated metabolites from human faeces were quantified by LC/UV and used as references for spiking human plasma samples. LC/MS/MS was applied to sensitively quantify docetaxel and its metabolites in human plasma using docetaxel calibration standards in a range of 0.25–500 ng/mL. RESULTS: Because ionisation of docetaxel and its metabolites differed, correction factors were established to quantify the metabolites using docetaxel calibration samples. During method validation, accuracy and precision of the metabolites were within ±7.7% and ≤17.6%, respectively, and within ±14.3% and ≤10.1%, respectively, for docetaxel. Metabolites were found to be unstable in human plasma at ambient temperature. After storage up to 1 year at –20 °C, recovered metabolite concentrations were within ±25%. CONCLUSIONS: Development and validation of an LC/MS/MS assay for the quantification of docetaxel and its metabolites M1/M3, M2 and M4 using docetaxel calibration standards is described. The same approach may be used for quantification of metabolites of other drugs by LC/MS/MS when chemically pure reference substances are unavailable. Copyright © 2013 John Wiley & Sons, Ltd.